2022
DOI: 10.3889/oamjms.2022.10830
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Prideness as a Nurse on the Extra Role Organizational Citizenship Behavior of Nurses at NU Hospital (RSNU) in East Java

Abstract: Background: During the current pandemic, it is necessary to continue to strengthen motivation and pride as a nurse as an effort to build nurses' commitment to realizing OCB. At this time the domestic nursing profession is required to be able to compete by improving the quality of nursing services. One of the bases for improving the quality of nursing services is that nurses must have a sense of pride as professional nurses with competencies that can answer internal and external challenges. Based on research on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In line with the ndings of this study, research conducted by [23] revealed that a signi cant proportion of employees reported moderate levels of job satisfaction. This consistency suggests that moderate levels of job satisfaction are prevalent across various organizational contexts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with the ndings of this study, research conducted by [23] revealed that a signi cant proportion of employees reported moderate levels of job satisfaction. This consistency suggests that moderate levels of job satisfaction are prevalent across various organizational contexts.…”
Section: Discussionsupporting
confidence: 88%
“…Employees who perceive that their work has a positive impact on others are more likely to experience higher levels of job satisfaction. Additionally, the freedom to use one's own judgment signi es autonomy and decisionmaking authority, which are key drivers of job satisfaction and motivation and are highly satis ed with 'freedom of working method' (mean = 6.46) and 'amount of variety in job' (mean = 6.18) [23]. When employees have the freedom to make decisions and exercise discretion in their work, they feel valued and empowered, leading to greater job satisfaction.…”
Section: Discussionmentioning
confidence: 99%